Diffusion of Agricultural Health and Safety Information: A Two Part Study of Oklahoma Farmers and Extension Agricultural Engineers - Judy B. Oskam (Journal of Applied Communications, 1995)
During the summer and fall of 1992, both on-site and mail surveys were conducted to determine: (1) How Oklahoma farmers receive and prefer to receive agricultural health and safety information from selected media and (2) How Extension agricultural engineering departments communicate agricultural health and safety information.